Intensification of crop rotation affecting weed communities and the use of herbicides in the rolling Pampa - De la Fuente, Elba Beatriz (2021)
Fil: De la Fuente, Elba Beatriz. Universidad de Buenos Aires. Facultad de Agronomía. Departamento de Producción Vegetal. Buenos Aires, Argentina.